Dimensions of Motivation in Student Self-Assessment: A Qualitative Perspective - Nabati, Shaghayegh; Mirshokraei, Ali Reza (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the multidimensional motivational factors influencing student engagement in self-assessment practices within higher education settings. A qualitative research design was employed, using semi-structured interviews with 15 university students from Tehran who had experience with self-assessment in academic contexts. Participants were selected purposively to ensure diversity across academic fields and educational levels. Data collection continued until theoretical saturation was reached. All interviews were transcribed verbatim and analyzed thematically using NVivo software to identify key categories, subcategories, and recurring conceptual codes. Thematic analysis revealed three major categories of motivational dimensions: intrinsic motivators, extrinsic influences, and self-regulatory processes. Intrinsic motivators included subthemes such as curiosity, self-directed goals, autonomy, competence, internal satisfaction, and reflective engagement. Extrinsic influences encompassed teacher expectations, peer comparison, family pressure, institutional culture, and recognition or rewards. Self-regulatory processes were reflected in goal-setting, effort monitoring, emotional regulation, feedback responsiveness, strategic learning behaviors, persistence, and adaptive help-seeking. While intrinsic motivation and autonomy enhanced authentic engagement with self-assessment, extrinsic motivators sometimes led to strategic or superficial involvement. Students who demonstrated higher levels of self-regulation tended to engage in deeper and more meaningful self-assessment practices. The findings suggest that motivational drivers are diverse, dynamic, and highly context-dependent. Student motivation in self-assessment is shaped by a complex interplay of internal drives, external pressures, and strategic behaviors. Educational environments that nurture autonomy, provide formative feedback, and emphasize growth-oriented learning can foster more authentic and effective engagement with self-assessment. Understanding the nuanced dimensions of student motivation can inform the design of more equitable, reflective, and learner-centered assessment practices in higher education.